Life cycle assessment and nutrient analysis of various processing pathways in algal biofuel production. (April 2017) - Mu, Dongyan; Ruan, Roger; Addy, Min; Mack, Sarah; Chen, Paul; Zhou, Yong
Highlights: A majority of fertilizers will eventually be discharged into the environment via wastewater. Pretreatment of HTL reduces NOx emissions but increase other impacts. Pretreatment of HTL reduces the cost of algal biofuel production. Abstract: This study focuses on analyzing nutrient distributions and environmental impacts of nutrient recycling, reusing, and discharging in algal biofuels production. The three biomass conversion pathways compared in this study were: hydrothermal liquefaction technology (HTL), hydrothermal hydrolysis pretreatment +HTL (HTP), and wet lipid extraction (WLE). Carbon, nitrogen, and phosphorous (C, N, P) flows were described in each pathway. A primary cost analysis was conducted to evaluate the economic performance. The LCA results show that the HTP reduced life cycle NOx emissions by 10% from HTL, but increased fossil fuel use, greenhouse gas emissions, and eutrophication potential by 14%, 5%, and 28% respectively. The cost of per gallon biodiesel produced in HTP was less than in HTL. To further reduce emissions, efforts should be focused on improving nutrient uptake rates in algae cultivation, increasing biomass carbon detention in hydrothermal hydrolysis, and/or enhancing biomass conversion rates in the biooil upgrading processes.